The Oxford Handbook of Superdiversity 2022
DOI: 10.1093/oxfordhb/9780197544938.013.18
|View full text |Cite
|
Sign up to set email alerts
|

Transnationalism, Elite Migrants, and the Spatiality of Superdiversity

Abstract: The geography or the spatiality of superdiversity has been only implicitly researched, primarily in ethnographic and sociolinguistic empirical studies on superdiversity. This chapter proposes a geographical conceptualization of superdiversity by analyzing sociospatial superdiversification as a process of bringing together the interconnected phenomena of the global increase of migration and the local transformation of urban spaces. By connecting the spatiality of superdiversity to the debates on the nexus of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…The aim of this article is to further develop the theoretical understanding of urban diversity, which encompasses literature on differential inclusion (Ye, 2016; Yeoh, 2006) but also on superdiversity (Meissner, 2015; Vertovec, 2007). By bringing together research on transnational professionals and expatriates (Beaverstock, 2013: 2917; Cranston, 2016), especially in the context of global cities (Yeoh and Chang, 2001; Yeoh and Willis, 2005), and delivering novel empirical data on an under-researched group of transnational corporate elites (at least regarding their socio-spatial patterns beyond their business roles), the article contributes both to the discussion of transnational professionals and their differential inclusion in cities and to the further contextual embedding into the debate on the ‘spatiality of superdiversity’ (Yamamura, 2022a).…”
Section: Socio-spatial Diversification and Transnational Migrationmentioning
confidence: 99%
See 3 more Smart Citations
“…The aim of this article is to further develop the theoretical understanding of urban diversity, which encompasses literature on differential inclusion (Ye, 2016; Yeoh, 2006) but also on superdiversity (Meissner, 2015; Vertovec, 2007). By bringing together research on transnational professionals and expatriates (Beaverstock, 2013: 2917; Cranston, 2016), especially in the context of global cities (Yeoh and Chang, 2001; Yeoh and Willis, 2005), and delivering novel empirical data on an under-researched group of transnational corporate elites (at least regarding their socio-spatial patterns beyond their business roles), the article contributes both to the discussion of transnational professionals and their differential inclusion in cities and to the further contextual embedding into the debate on the ‘spatiality of superdiversity’ (Yamamura, 2022a).…”
Section: Socio-spatial Diversification and Transnational Migrationmentioning
confidence: 99%
“…The concept of ‘commonplace diversity’ (Wessendorf, 2013) describes the development of high levels of conviviality and inclusivity in urban space to a degree that ‘ethnic, religious and linguistic diversity [is] experienced as a normal part of social life and not as something particularly special’ (Wessendorf, 2013: 407). While it is suggested that ‘social spaces […] play an important role in the process of familiarisation with people who are different and in getting accustomed to communicating across difference’ (Wessendorf, 2013: 410), the urban spaces and the differential inclusion in cities remain abstract and the actual ‘spatiality of superdiversity’ (Yamamura, 2022a) under-researched.…”
Section: Socio-spatial Diversification and Transnational Migrationmentioning
confidence: 99%
See 2 more Smart Citations
“…The interesting aspect of these intermediaries is, in fact, that there is a clear diversification happening, which might also be the key to understanding the spatial diversification in specific arrival cities through migration industries. Indeed, while the diversification of the urban population and urban spaces themselves has been well acknowledged in migration research (Meissner and Vertovec, 2014; Yamamura, 2022a), the diversification of migration industries in accordance with the diversifying migration streams has only recently come into focus (Gammeltoft-Hansen and Sørensen, 2013; Garapich, 2008). As much as debates on migration industries stem from more migration policy related fields (cf., Gammeltoft-Hansen and Sørensen, 2013; Jones and Sha, 2020), the context to the urban space and its shaping through migration industries, however, is still an underexplored field.…”
Section: Literature Reviewmentioning
confidence: 99%